Case Report: Intermittent Chest Pain With Cough, Fever, and Pericardial Effusion Over the Course of 1 Year in an 11-Year-Old Girl - Jing Chen; Lu Qin; Lan-Fang Tang (Frontiers Media S.A., 2022)
An 11-year-old girl presented with frequent chest pain, fever, and a cough that she had had for more than 13 months, as well as pleural effusion and large pericardial effusion. She was misdiagnosed with tuberculosis and received anti-tuberculosis drugs for 6 months. Within the past year, she also underwent two more thoracotomies and a thoracoscopic partial pericardiectomy. The final diagnosis of pulmonary paragonimiasis was established once it was known that she had eosinophilia, always drank stream water, and tested positive for antibodies against Paragonimus. Since antiparasitic praziquantel therapy was effective, paragonimiasis should be considered as a possibility in the differential diagnosis of tuberculosis in children.